Ökonomische Bildung für eine nachhaltige Entwicklung Eine phänomenographische Untersuchung in der Lehrerinnenbildung - Löw Beer, David (Verlag Barbara Budrich, 2016)
How can economic education enable us to shape a sustainable transformation of our economic system in the face of man-made social and ecological crises? The author prepares models from Ecological Economics and Environmental Economics for educational processes, analyzes pre-concepts of students of Economic Education, and brings together scientific models and learners' ideas to form seminar concepts.